HUBUNGAN IKLIM KERJASAMA DENGAN SEMANGAT KERJA PEGAWAI PADA DINAS PENDIDIKAN KOTA SOLOK - Elvi Nofrida (Universitas Negeri Padang, 2014)
This study aimed to obtain information about: (1) employee morale at Solok City Department of Education, (2) Climate Cooperation in Solok City Department of Education, (3) climate cooperation relationship with employee morale at Solok City Department of Education. The hypothesis of the proposed research is “climate of cooperation correlate significantly with employee morale at Solok City Department of Education. The present study is correlational, which is to see the climate of cooperation relationship with employee morale at Solok City Department of Education. The population of this research is an employee who is a civil servant in Solok City Department of Education totaling 74 people. Large study sample was 50 persons specified by proportional stratified random sampling technique. The instrument used for data collection was a questionnaire type a Likert scale that have been valid and reliabel. The technique of data analysis is done by using the formula Product Moment Correlation and T-test. The results of the data analysis showed that (1) Morale in Solok City Department of Education is in the category is quite (77,27%), (2) Climate cooperation in Solok City Department of Education are on the category is quite (79,24%), and (3) there is a significant relationship to climate between cooperation with employee morale at Solok City Department of Education with a correlation coefficient = 0,71 r_hitung > r_tabel = 0,279 at 95% confidence level and t_hitung = 7,03 > t_tabel 2,021 at 95% confidence level. So it can be concluded that the cooperation climate affects employee morale at Solok City Department of Education. Kata kunci: Iklim kerjasama dan semangat kerja